Comparative assessment of modern parameters of glycemic control in children with type 1 diabetes after switching to fast-acting insulin aspart using Flash Glucose Monitoring in real clinical practice - Y. V. Girsh; A. V. Kiyaev; M. A. Slovak; I. V. Korneva; I. A. Promin; N. A. Yusupova; L. I. Savelyev (Сахарный диабет)
BACKGROUND: Postprandial hyperglycaemia contributes significantly to the lack of glycaemic control in patients with type 1 diabetes mellitus (DM1). At least a quarter of patients forget to inject insulin before meals once a week, and more than 40% of them inject bolus insulin immediately before meals, which does not correspond to the pharmacokinetic effects of ultrashort insulins and determines the need to use insulins with better imitations of physiological insulin secretion.AIM: To assess the effect of fast acting insulin aspart (FIAsp) on the current parameters of glycaemic control in children with DM1 after switching from insulin Asp (iAsp) using continuous glucose monitoring.MATERIALS AND METHODS: A multicenter observational 12-week prospective open-label uncontrolled comparative study was initiated. A group of insufficiently controlled patients were identified (n = 48) including a group on multiple insulin injections therapy (MII) (insulin degludec and IAsp) and a group on continuous subcutaneous insulin infusion (CSII) of iAsp. Three 14-day flash glucose monitoring (FMG) were performed: before transferring patients to FiAsp and after 2 and 12 weeks of the transfer. Key endpoints: HbA1c after 2 and 12 weeks on FiAsp relative to baseline, analysis of 5 FMG target glucose ranges, presented as an ambulatory glycemic profile. Additional indicators: dynamics of insulin daily dose, frequency of glucose self- monitoring, the number of severe hypoglycemia, adverse events that occurred during treatment.RESULTS: 2 weeks after the transfer from IAsp to FIAsp, TIR increased in the entire group of patients: from 53% [44.3; 66.5] to 57% [47.4; 71.0] (p-value = 0.010) and TAR decreased from 38% [24.8; 50.2] to 30.5% [22.0; 45, 0] (p-value = 0.0124). Maintaining and increase time spent in the target glucose ranges during a 12-week observation period, in parallel with a significant decrease in hypoglycemic episodes <3.9 mmol / L per week, on FIAsp therapy naturally leads to an improvement in diabetes control: a decrease in HbA1c from 8.15% up to 7.75% (p-value = 0.0224), more pronounced in the group of patients on CSII — from 7.9% to 7.5% (p-value = 0.028).CONCLUSION: Switching from IAsp to BDIAsp in routine clinical practice in the MII and CSII regimen in children and adolescents with type 1 diabetes allows achieving better glycemic control compared to the previous generation prandial insulin analog Iasp. The better diabetes control is associated with an increase or a trend towards an increase in TIR and a decrease or a trend towards a decrease in TAR and TBR, as well as a significant decrease in episodes of hypoglycemia.